Strategic behavior in digital reading in english as a second/foreign language: a literature review - do Amaral, Juliana; Torres, Marília Camponogara; Tomitch, Lêda Maria Braga (BELT - Brazilian English Language Teaching Journal, 2018)
This paper aims at presenting an overview of recent studies on students’ strategic behavior while reading online texts in English as a second/foreign language. As the digital environment has unique features that may influence reading comprehension, it is necessary that readers develop strategies to better cope with the online demands (Leu et al., 2014; Cho & Afflerbach, 2017). The studies here described made use of a wide range of data collection procedures, approaching qualitative and quantitative methods, by using surveys, observations, interviews and think-aloud protocols. Their findings collaborate to the understanding that Internet/hyperlinked reading is a complex cognitive process, involving not only the transfer of paper-based strategies but also mastering computer and multimedia skills